Fecal biomarkers of environmental enteric dysfunction and the gut microbiota of rural Malawian children: An observational study. Issue 10 (October 2021) - Chaima, David; Pickering, Harry; Hart, John D.; Burr, Sarah E.; Maleta, Kenneth M.; Kalua, Khumbo; Bailey, Robin L.; Holland, Martin J.
Abstract: Environmental enteric dysfunction (EED) is a subclinical condition of the gut characterized by changes in morphology and function with underlying chronic inflammatory responses. This study characterized composition and diversity of the gut microbiota in rural Malawian children with and without signs of EED. Fecal samples were collected from children aged 1–59 months. Neopterin, myeloperoxidase and alpha-1 antitrypsin concentrations were quantified by ELISA and combined to form a composite EED score using principal component analysis. DNA was extracted from fecal samples and V4-16S rRNA gene sequencing was used to characterize the gut microbiota. The concentrations of all three biomarkers decreased with increasing age, which is consistent with other studies of children living in similar low-income settings. Firmicutes, Bacteroidetes, Proteobacteria and Actinobacteria were the dominant phyla while Faecalibacterium and Bifidobacterium were the most prevalent genera. Increased alpha diversity was associated with a reduction in neopterin concentration. Microbiota composition was different between fecal samples with low and high composite EED scores; increased abundance of Succinivibrio was associated with reduced composite EED scores. Highlights: Fecal concentrations of myeloperoxidase, alpha-1 antitrypsin and neopterin decreased with age in Malawian children. A marginal negative association was found between alpha diversity of the gut microbiota and fecal neopterin concentration. Succinivibrio abundance was higher in children with reduced composite environmental enteric dysfunction biomarker score. Modelling found 3 metagenomic-metabolic pathways associated with a reduced risk of high composite biomarker score. Abstract : Gut microbiota; V4-16S rRNA sequencing; PICRUSt2; Environmental enteric dysfunction.